Academic Language Functions In Arabic Research Articles - Norhayuza Mohamad; Mohamad Nor Amin Samsun Baharun; Mohd Akashah Mohamad Yusof (Ijaz Arabi Journal of Arabic Learning, 2022)
A language is a communication tool that has many functions. In academic writing, language performs certain functions, such as providing information, analyzing, comparing, and categorizing. Quality academic writing should show proper educational function through accurate and appropriate language. This study investigated academic language functions in Arabic language research articles. This study is based on several issues, such as the weaknesses of students and researchers in producing quality research reports, the need to understand the diversity of the academic language function in Arabic, as well as the lack of studies in the literary language based on the function of the academic language in Arabic. This study uses the descriptive qualitative approach and content analysis method. The analyzed content was sentenced that contained academic language functions. Sentences containing academic language functions were taken from 30 research articles in the field of Arabic written by native Arabic speakers. The analysis of language functions in the study was done using 12 academic language functions by Chamot and O'Malley (1994) and Dutro and Muran (2003). The study results found that writers use various academic functions to achieve the desired purpose. Various language registers are used for the function to be presented. Similarly, the use of language functions was also influenced by multiple aspects such as the research components (problem statement, objectives, etc), factors of the type of study (quantitative and qualitative), and others. For example, predicting and hypothesizing functions and problem-solving functions are more likely to be used in quantitative studies. This differs from qualitative studies that use other functions, such as informing and summarizing. In conclusion, the writers were seen to be successful in conveying the function of academic language in their writing by using appropriate vocabulary and sentences according to the function they wanted to share.